2023
DOI: 10.1111/his.14863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation oncotype DX® 21‐gene recurrence score and clinicopathological parameters: a single institutional experience

Abstract: Aims: Oncotype DX recurrence score (RS) is a clinically validated assay, which predicts the likelihood of disease recurrence in oestrogen receptor-positive/ HER2-negative (ER+/HER2À) breast cancer (BC). In this study we aimed to compare the performance of Oncotype DX against the conventional clinicopathological parameters using a large BC cohort diagnosed in a single institution. Methods and results: A cohort (n = 430) of ER+/ HER2À BC patients who were diagnosed at the Nottingham University Hospitals NHS Trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In our recent study, we found a strong positive correlation between Oncotype DX RS and Ki67 and none of the patients with less than 10% Ki67 expression had high risk Oncotype DX RS while in high Ki67 expression tumours, Oncotype DX RS varies. For example, 54% of tumours with Ki67 >70% has high risk RS compared to 17% that showed low risk RS, supporting the reliability of Ki67 in predicting tumour prognosis and Oncotype DX 83 . In addition, a previous study showed that high Ki67 tumours are at higher risk of relapsing among patients with low risk Oncotype DX, and Ki67 status may help to identify a subset of low risk Oncotype DX patients who could benefit from adjuvant chemotherapy 86 .…”
Section: Ki67 and Molecular Subtypesmentioning
confidence: 81%
See 1 more Smart Citation
“…In our recent study, we found a strong positive correlation between Oncotype DX RS and Ki67 and none of the patients with less than 10% Ki67 expression had high risk Oncotype DX RS while in high Ki67 expression tumours, Oncotype DX RS varies. For example, 54% of tumours with Ki67 >70% has high risk RS compared to 17% that showed low risk RS, supporting the reliability of Ki67 in predicting tumour prognosis and Oncotype DX 83 . In addition, a previous study showed that high Ki67 tumours are at higher risk of relapsing among patients with low risk Oncotype DX, and Ki67 status may help to identify a subset of low risk Oncotype DX patients who could benefit from adjuvant chemotherapy 86 .…”
Section: Ki67 and Molecular Subtypesmentioning
confidence: 81%
“…The St Gallen guidelines recommended Ki67 in order to distinguish the molecular subtypes luminal A and luminal B BC 11. Due to its prognostic significance in hormone receptor-positive BC, MKi67 gene is one of the 16 genes that are measured in the Oncotype DX recurrence score (RS) 76–78. There is a high concordance rate between Oncotype DX RS and Ki67 index 36 79 80.…”
Section: Ki67 Assessmentmentioning
confidence: 99%
“…BC is the leading cause of cancer‐related deaths in women worldwide and the therapeutic decision of BC patients currently depends on histopathological data and molecular biomarkers 26,39–41 . However, many patients show resistance to treatment due to the clinical heterogeneity of BC 42 .…”
Section: Discussionmentioning
confidence: 99%
“…BC is the leading cause of cancer-related deaths in women worldwide and the therapeutic decision of BC patients currently depends on histopathological data and molecular biomarkers. 26,[39][40][41] However, many patients show resistance to treatment due to the clinical heterogeneity of BC. 42 For these reasons, research into the molecular biology of treatment response is often aimed at identifying genes with prognostic and predictive impact, especially for TNBC patients, who do not benefit from targeted therapy and show a high rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to determine the correlation between RS and various predictive clinicopathological indicators, including the expression of estrogen receptor (ER) and progesterone receptor (PR), high histologic grade, and Ki-67 proliferation index, which have yielded a variety of models ( 8 - 12 ). However, the predictive performance has varied widely across studies, with the accuracy ranging from 52.5–86.8%.…”
Section: Introductionmentioning
confidence: 99%